More hemodynamic changes in hypertensive versus non-hypertensive patients undergoing breast cancer surgery in general anesthesia - a prospective clinical study - Darija Azenić-Venžera; Kata Šakić; Jozo Kristek; Ivana Drenjančević-Haršanji; Andreja Rakipović-Stojanović; Gordana Brozovic; Slavica Kvolik; Dražen Vidović; Borna Kovačić; Gordana Kristek (Medicinski Glasnik, 2009)
Aim Preoperative comorbidity may significantly influence theconduction of anesthesia and patients’ outcome. The aim of thisstudy was to compare a number of anesthetic interventions and theuse of non-anesthetic drugs in hypertensive and non-hypertensivepatients during general anesthesia for moderately invasive surgery.Methods A total number of 88 elective hypertensive (n = 44) andnon-hypertensive (n = 44) breast cancer patients were enrolled inthe prospective study. Midazolam and infusion of normal salinewere given before anesthesia. Etomidate, rocuronium, fentanyl,and sevoflurane up to the 1 MAC were used for the maintenanceof anesthesia. Mean arterial pressure (MAP), pulse, core temperatureand intraoperative use of all drugs were recorded. MAPwas maintained by sevoflurane and infusion replacement. Urapidiland ethylephrine were given if MAP differed > or <30% ofbaseline, and atropine if heart rate <50 beats min-1. A statisticalanalysis was made using chi-square and Mann-Whitney tests.Results The highest MAP was 133±19.3 in hypertensive and 122±16.5mmHg in the non-hypertensive patients (p<0.05). Hypertensive patientsrequired more anesthetic balancing (42 vs. 23 interventions),more urapidil for intraoperative hypertension (13/44 vs. 2/44, p<0.05) and had more intraoperative hypotensive episodes (23 vs. 12;ns, p> 0.05). Intraoperative bradycardia (11/44 vs.7/44) and atropineapplications (16 vs. 9, ns, p> 0.05) were similar in two groups.Conclusion Hypertensive patients required more anesthetic interventionsand had higher consumption of vasoactive drugs duringanesthesia for breast cancer surgery, suggesting their hemodynamicinstability possibly related to the hypertension.